Network-based insights into miR-30a-5p-mediated regulation and EGCG targeting in triple-negative breast cancer - Dharshini, Loganathan Chandramani Priya; Mandal, Abul Kalam Azad (Frontiers in Bioinformatics, 2025)
BackgroundTriple-negative breast cancer (TNBC) is defined by the absence of ER, PR, and HER2 expression. This limits the targeted therapies, resulting in poor clinical outcomes. Identifying the molecular targets that can be regulated through miRNAs and natural compounds offers a potential therapeutic platform.MethodsWe combined transcriptomic profiling with miRNA target prediction to identify genes regulated by miR-30a-5p and assess their interaction with the green tea polyphenol, epigallocatechin gallate (EGCG). Differentially expressed genes (DEGs) from TCGA-TNBC datasets and miRNA targets from miRDB, TargetScan, and miRTarBase were screened for common genes. Then, the protein-protein interaction and network topology analyses were performed to identify key hub genes. Molecular docking and simulation were carried out with the four key genes against EGCG.ResultsData integration yielded 393 overlapping genes and identified ten hub genes- RRM2, KIF11, ANLN, CDC20, CCNA1, AGO2, YWHAZ, DTL, SKP2, and PCNA. Pathway enrichment showed that all these hubs are involved in cell cycle and mitotic regulation, which was associated with poor TNBC prognosis. Mutation profiling revealed high alteration rates in KIF11, ANLN, CDC20, and YWHAZ, with increased missense mutations and C>T transitions. Molecular docking and simulations identified YWHAZ as the most favorable and structurally stable EGCG-binding target, compared to the other three key genes.ConclusionThe results emphasizes that EGCG has strong binding affinity towards YWHAZ, revealing that miR-30a-EGCG targets TNBC synergistically through cell-cycle-mediated pathways. The findings give rational support for miRNA-guided phytochemical-based TNBC therapeutic development.